Pengaruh Metode Jarimatika terhadap Hasil Belajar Matematika pada Siswa Kelas 3 SDN 13 Parittiga Bangka Barat - Puput, Puput Atmasari; Asyraf Suryadin; Yorenza Meifinda (JBES (Journal Basic Education Skills), 2024)
This research was motivated by students' low mathematics learning outcomes, especially in fraction material, as well as other factors, namely that during learning activities, the learning methods used by teachers were less varied, making students less likely to understand fraction material. This research aims to determine how the Jarimatics method affects mathematics learning outcomes for grade 3 students at SDN 13 Parittiga, West Bangka. This research uses quantitative research with a "Quasi-Experimental Design" research design in the form of "Pretest and Posttest with Nonequivalent Control Group Design." The sample in this study consisted of 40 third-grade students at SD Negeri 13 Parittiga. The data collection technique used was a test consisting of 11 test questions with short answers. The data analysis techniques used are normality tests, homogeneity tests, and hypothesis tests using the independent sample t-test. The research results show that hypothesis testing using the independent sample t-test with the polled variance formula obtained t-count > t-table, namely t-count = 2.437 and t-table = 2.024. This indicates that Ho is rejected and Ha is accepted. From the results of the data analysis, it can be concluded that using the Jarimatika method influences mathematics learning outcomes for grade 3 students at SDN 13 Parittiga, West Bangka.